Efektivitas Penggunaan Media Kartu Kata Bergambar berbasis Budaya Lokal terhadap Keterampilan Membaca Permulaan Murid Kelas II SDN Gugus 5 Kecamatan Praya - Nur Mahmudi Insani; Syaiful Musaddat; Syarifuddin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Early reading skills are one of the most important skills for students in elementary school. However, in reality, many students are still unable to master this early reading skill. This study aims to determine the effectiveness of using picture word cards based on local culture on the early reading skills of second-grade students of Elementary School Gugus 5, Praya District. This study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research subjects consisted of all second-grade students of Elementary School Bunsalak and Elementary School Jago, totaling 78 people. The data collection technique used an early reading skills performance test. Data were analyzed using prerequisite tests, hypothesis tests, and N-Gain tests. Hypothesis testing was carried out using an independent sample t-test which showed a significance value (2-tailed) of 0.001 <0.05, which means there is a significant difference between the experimental class and the control class. Then, seen from the results of the N-Gain test of 0.57, it is in the moderate category. Based on this, Ho is rejected and Ha is accepted, which shows that the use of local culture-based picture word cards is effective in improving the early reading skills of second-grade students at SDN Gugus 5, Praya District.